2020
DOI: 10.3390/app10062193
|View full text |Cite
|
Sign up to set email alerts
|

Surface Radiation Balance of Urban Materials and Their Impact on Air Temperature of an Urban Canyon in Lisbon, Portugal

Abstract: Urban climate results from the modifications caused by the characteristics of cities, which modifies the regional climatic conditions of a city. When urban areas are warmer than the surrounding areas, the urban heat island (UHI) phenomenon occurs. Being a major phenomenon and a global topic of interest for all affected cities, there are already numerous studies that address this subject. However, most studies are only focused on the macro and mesoscales. This study looks at the micrometeorological scale in a n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 12 publications
0
8
0
Order By: Relevance
“…We measured heat index-the combination term for air temperature and relative humidity that captures what the temperature feels like [30]-by semi-permanently installing 10 HOBO MX2302A external air temperature/ relative humidity sensor data loggers (Onset Computer Corporation, MA) at each park. Previous studies have used comparable networks of in situ sensors to monitor microclimatic conditions of a given area [31][32][33]. Measurement of near-surface air temperatures is advantageous over the use of land surface temperatures as a proxy for air temperatures, as research has shown land surface temperatures are not directly comparable to air temperatures [34,35].…”
Section: Measurement Of Heat Indexmentioning
confidence: 99%
“…We measured heat index-the combination term for air temperature and relative humidity that captures what the temperature feels like [30]-by semi-permanently installing 10 HOBO MX2302A external air temperature/ relative humidity sensor data loggers (Onset Computer Corporation, MA) at each park. Previous studies have used comparable networks of in situ sensors to monitor microclimatic conditions of a given area [31][32][33]. Measurement of near-surface air temperatures is advantageous over the use of land surface temperatures as a proxy for air temperatures, as research has shown land surface temperatures are not directly comparable to air temperatures [34,35].…”
Section: Measurement Of Heat Indexmentioning
confidence: 99%
“…Study staff recorded in the Comments section of the SOPARC data collection form whether it was raining while conducting observations (Figure A2). We measured heat index by installing 10 HOBO MX2302A external air temperature/relative humidity sensor data loggers (Onset Computer Corporation, Bourne, MA, USA) at each park, per previous studies [51,52]. We then calculated heat index using equations from the US National Weather Service [53].…”
Section: Measurement Of Variables That May Impact Park Use By Childrenmentioning
confidence: 99%
“…We measured heat index-the combination term for air temperature and relative humidity that captures what the temperature feels like (24)-by semi-permanently installing 10 HOBO MX2302A external air temperature/relative humidity sensor data loggers (Onset Computer Corporation, MA) at each park. Previous studies have used comparable networks of in situ sensors to monitor microclimatic conditions of a given area (25)(26)(27). Measurement of near-surface air temperatures is advantageous over the use of land surface temperatures as a proxy for air temperatures, as research has shown land surface temperatures are not directly comparable to air temperatures (28,29).…”
Section: Measurement Of Heat Indexmentioning
confidence: 99%